Developing a Framework of Pedagogical Content Knowledge on Arithmetic for the Primary School Teachers of Mizoram - Mishra, Lokanath (INDIAN EDUCATIONAL REVIEW, 2020)
In order to live life to the fullest and in an effective way, quality of education is very important. Teachers are liable for delivering best knowledge for the welfare of people, society and the whole nation. Pedagogical Content Knowledge (PCK) helps teachers to transmit their knowledge to the students in an effective way. Having in-depth knowledge and understanding about the content is not enough to be a good teacher, they should be able to communicate it with the students effectively. Therefore, the knowledge of pedagogy is crucial for classroom instruction. Teachers should possess the skills to deliver the content in the most simple and easy way that can be understood by the students. In the process of teaching and learning it’s not only students whose lack of understanding of concepts sometimes create misconception, it may also be due to the teacher’s wrong delivery of concepts, especially in subjects like arithmetic. Misconceptions are not new in arithmetic but in-depth understanding and vigorous skills of teachers will help to eliminate those misconceptions. According to Shulman (1987, p. 8), PCK is that special amalgam of content and pedagogy that is uniquely the providence of teachers, their own special form of professional understanding. PCK identifies the distinctive bodies of knowledge for teaching. It represents the blending of content and pedagogy into an understanding of how particular topics, problems, or issues are organised, represented, and adapted to diverse interests and abilities of learners, and presented for instruction. PCK is the category most likely to distinguish the understanding of the content specialist from that of the pedagogue.